2022
DOI: 10.1177/23333936221085035
|View full text |Cite
|
Sign up to set email alerts
|

How do Professionals in Municipal Health and Welfare Relate to Bereaved Persons During the Acute Phase of a Drug-Related Death? A Qualitative Study

Abstract: This study aims to broaden our knowledge of how professionals in municipal health and welfare relate to bereaved persons during the acute phase of a drug-related death. A reflexive thematic analysis was applied to six focus group interviews with 27 first responding personnel in Norway. The article describes the complexity and simultaneousness of the professional response. Three main themes were identified: (a) establishing contact, (b) diverse, supportive assistance, and (c) a complex helping context. The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…The study results show that pre-existing relationships with the bereaved persons concerned are perceived as an important condition for the provision of help and for professionals' helping initiatives being accepted. This study's findings differ from those of Løseth et al (2022), who explore the experiences of first responders encountering the DRD bereaved in Norway and finds that relationships established before death can obstruct help provision. These divergent findings can probably be explained by the multiple and conflicting positions of help and control (eg of child welfare worker and crisis team member) occupied by some of the first responders in the study by Løseth et al (2022).…”
Section: Bereavement Support Relies On Individualised Relationships A...contrasting
confidence: 99%
See 1 more Smart Citation
“…The study results show that pre-existing relationships with the bereaved persons concerned are perceived as an important condition for the provision of help and for professionals' helping initiatives being accepted. This study's findings differ from those of Løseth et al (2022), who explore the experiences of first responders encountering the DRD bereaved in Norway and finds that relationships established before death can obstruct help provision. These divergent findings can probably be explained by the multiple and conflicting positions of help and control (eg of child welfare worker and crisis team member) occupied by some of the first responders in the study by Løseth et al (2022).…”
Section: Bereavement Support Relies On Individualised Relationships A...contrasting
confidence: 99%
“…Knowledge about professionals' own experience helping individuals grieving a DRD and the resources they need to respond adequately is lacking (Reime et al, 2022). A recent Norwegian study of psycho-social follow-up immediately after DRD found that first responders often fail to include the DRD bereaved in the provision of services (Løseth et al, 2022). showed that symptoms of complicated grief were highest among those who had lost someone one to two years earlier, underscoring the importance of long-term help provision and the importance of professionals being aware of the symptoms of complicated grief over a longer time span.…”
Section: Discrepancy Between Support Needs and Support Provisionmentioning
confidence: 99%
“…Previous research shows that the bereaved experience complex help systems (Løseth et al, 2022; Templeton, Valentine, et al, 2017; Valentine et al, 2018). Attending to sudden and unnatural deaths requires the provision of services affiliated with various professions and institutional divisions, including medical first response, police investigation, care of the dead body and follow-up for the bereaved.…”
Section: Barriers Relating To Complex Service Structuresmentioning
confidence: 99%
“…A recent study has shown that first-responder professionals are essential in making referrals for further follow-up in the acute phase (1–4 weeks after death) in the municipalities (Løseth et al, 2022). In line with Kalkman (2020), the study also showed that establishing contact could be challenging because of the restricted timeframe and complex organisational premises, as in ordinary frontline work (Løseth et al, 2022). It is of vital importance to obtain more research-based knowledge from first-attending professional helpers in the acute phase in order to improve the services for psychosocial follow-up for those bereaved by a DRD.…”
mentioning
confidence: 99%
See 1 more Smart Citation